ANALISIS KEPUASAN PELANGGAN DENGAN MENGGUNAKAN METODE STRUCTURAL EQUATION MODELING (SEM) DAN QUALITY FUNCTION DEPLOYMENT (QFD) DI PT. XYZ - Adella Nurha Almaidani (2021)
Satisfaction. Customer satisfaction at PT. XYZ is also the orientation of the company. However, at this newly established company there is no assessment related to customer satisfaction, so it cannot evaluate what factors cause customer satisfaction and what factors or things can relate to customer satisfaction. The thing that has an influence on service quality is customer trust and can be influenced by service quality. Using the structural equation modeling method can make it easier to find out the value or level of influence between variables. From these results can help evaluate the company by using the Qualty Function Deployement (QFD) method to create a strategy to increase customer satisfaction with the House of Quality (HOQ).